Seizure, tetanic spasm and primary hypoparathyroidism - Dhungana, Arun; Singh, J N; Singh, A. R.; Sapkota, S.; Pokharel, Baburam (Journal of Kathmandu Medical College, 2014)
Primary hypoparathyroidism is not a common disease, and it is not a common cause of seizures. Here we present a 21-year-old female with hypoparathyroidism who presented with tetanic spasm and seizure. Her parathyroid hormone level was low, Calcium level was low and Phosphorus was increased. Electroencephalogram showed sharp spike and Computed Tomography scan showed multiple symmetrical calcification in the basal ganglia, thalamus, cerebellum, cerebral hemisphere and periventricular region. With these features, our provisional diagnosis was Fahrs syndrome. Patient was treated with calcium gluconate and anticonvulsant. Patient improved and was discharged on medication. DOI: http://dx.doi.org/10.3126/jkmc.v2i2.10633 Journal of Kathmandu Medical College, Vol. 2, No. 2, Issue 4, Apr.-Jun., 2013, Page: 94-96